Study of River/Channel Normalization Planning Lines and River Boundaries in the Cibeunying SWK Area, Bandung City - Ina Revayanti (Jurnal Ragam Pengabdian, 2026)
The rapid growth of Bandung City, triggered by urbanization and vertical development, has led to significant land use change, requiring more adaptive spatial planning. This study focuses on evaluating the River/Channel Normalization and River Boundary Plan in the Cibeunying Sub-District (SWK). The main issue raised is the sedimentation and silting of rivers due to increased development in the housing, trade, and service sectors, which has changed the land use around waterways. The research method was carried out by superimposing technical plan maps (developed since 1988) with existing land use and integrating the latest housing site plans. Data transformation also involved migration from manual to digital maps integrated with the 2016 base map recommended by the Geospatial Information Agency (BIG). The results of this evaluation serve as geometric guidelines for spatial utilization control, particularly in the issuance of Spatial Planning Activity Suitability (KKPR) recommendations and site plans. This arrangement is expected to create integrated and sustainable infrastructure planning between built-up areas and the river network in the Cibeunying SWK.